2015
DOI: 10.1364/boe.6.004154
|View full text |Cite
|
Sign up to set email alerts
|

Optical clearing based cellular-level 3D visualization of intact lymph node cortex

Abstract: Lymph node (LN) is an important immune organ that controls adaptive immune responses against foreign pathogens and abnormal cells. To facilitate efficient immune function, LN has highly organized 3D cellular structures, vascular and lymphatic system. Unfortunately, conventional histological analysis relying on thin-sliced tissue has limitations in 3D cellular analysis due to structural disruption and tissue loss in the processes of fixation and tissue slicing. Optical sectioning confocal microscopy has been ut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 42 publications
(56 reference statements)
0
31
0
Order By: Relevance
“…The detection and photothermal treatment of nonpigmented breast cancer cells in sentinel lymph nodes were achieved by previous labeling them with nanoparticles. In this study and in recent work,33 the enhancement of imaging depth in lymph nodes were demonstrated by using of optical clearing techniques.…”
mentioning
confidence: 65%
“…The detection and photothermal treatment of nonpigmented breast cancer cells in sentinel lymph nodes were achieved by previous labeling them with nanoparticles. In this study and in recent work,33 the enhancement of imaging depth in lymph nodes were demonstrated by using of optical clearing techniques.…”
mentioning
confidence: 65%
“…Recent progress in TOC and imaging opens new avenues to study cells phenotype and distribution within transparent, entire intact lymph nodes, an approach called histocytometry. Until now FocusClear, CUBIC, SeeDB, CLARITY, BABB, and uDISCO were used for lymph nodes clearing, with one study describing a completely new method for their clearing, C e 3D . C e 3D is the first approach to utilize N ‐methylacetamide with histodenz for TOC, a solution selected from 32 tested possible OCAs.…”
Section: Application Of Toc For Particular Peripheral Organsmentioning
confidence: 99%
“…For in vivo video-rate cellular-level monitoring of ICG pharmacokinetic dynamics, a custombuilt video-rate laser-scanning confocal microscopy system previously described [37][38][39][40][41][42] was modified for simultaneous imaging of green and near infrared ICG fluorescence imaging as shown in Fig. 1(a).…”
Section: Near-infrared Laser-scanning Confocal Microscopy Systemmentioning
confidence: 99%